Cooling dynamics of carbon cluster anions. (November 2015) - Shiromaru, H; Furukawa, T; Ito, G; Kono, N; Tanuma, H; Matsumoto, J; Goto, M; Majima, T; Sundén, A E K; Najafian, K; Pettersson, M S; Dynefors, B; et al.
Abstract: A series of ion storage experiments on small carbon cluster anions was conducted to understand size-dependent cooling processes. The laser-induced delayed electron detachment time profile show clear even/odd alternation due to the presence of the electronic cooling. The time evolution of the internal energy distribution was simulated for Cn - (n=4 to 7) with a common procedure taking vibrational and electronic cooling into account.